ANALISIS PERSEPSI DOSEN TENTANG PENGARUH KECERDASAN SUMBER DAYA MANUSIA TERHADAP KINERJA PERUSAHAAN - Slamet Wiyono (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
This is an exploration research. The research aims to know lecturer perception of Economic Faculty University about the effect of SQ/EQ/iq to performance of organisation/institution. The other objective of the research is finding dominant factor influenced performance ofthe institution. The research used Kruskal Wallis Test to test hypothesis with alpha 0,05 . The result of this research showed there were no significant perception of 14 variables had been examined. It means there was no differentiation perception ofthe respondents. The other result of the research showed the three dominant factor that influenced performance of organisation are SQ factor: honesty with mean 2,-35, EQ factor: emphaty with mean 2,45, and IQfactor :creativity with mean 2,45.